Assessing the Effect of Polypropylene on the Durability of Flexible Pavements - Douglas Mivule (Uganda Christian University, 2025)
One of the primary factors influencing deterioration and failure in flexible pavements is the tensile strength of asphalt mixtures. Therefore, the impacts of reinforcing asphalt mixtures with polypropylene fibres on their engineering performance were examined experimentally in this work. In order to assess the indirect tensile stiffness modulus, a series of cylindrical asphalt mixture specimens were constructed and put under compression load at various testing temperatures. Tests for fatigue and fracture propagation were also carried out for various asphalt mixtures with and without polypropylene fibres. These fibres' effects on the engineering characteristics of asphalt mixtures were investigated. Tensile, fatigue, and cracking initiation and propagation were all significantly impacted by the reinforced mixes containing polypropylene fibres, according to the laboratory data.